Active power filtering using interlinking converter in droop controlled islanded hybrid AC‐DC microgrid. (5th February 2020) - Shravan, R.V.S.E.; Vyjayanthi, C.
Summary: In a hybrid AC‐DC microgrid, the interlinking converter (IC) is used for tying AC and DC subgrids as the medium of power transfer between the two subgrids. Within an islanded hybrid microgrid (HMG) power transfer between droop controlled AC and DC subgrids is done through IC to achieve power sharing between the subgrids. Further, in this paper, a modified control strategy for IC is proposed for carrying out active power filtering also. Under non‐linear loading conditions, IC in conjunction with the DC subgrid can be used as an active power filter (APF), to filter the AC side line currents and to maintain a sinusoidal voltage at the AC bus. This type of control of the IC in an islanded HMG is so far not much investigated. In this paper, an HMG is simulated in MATLAB/Simulink for different loading conditions, considering linear and non‐linear loads and various set of simulation studies are presented for validating the effectiveness of the proposed control strategy. The system is also implemented using real‐time digital simulator hardware, and the obtained results are presented to support the efficacy of the proposed control strategy.